Injury of the Carotid Artery during Endoscopic Endonasal Surgery: Surveys of Skull Base Surgeons - Rowan, Nicholas R.; Turner, Meghan T.; Valappil, Benita; Fernandez-Miranda, Juan C.; Wang, Eric W.; Gardner, Paul A.; Snyderman, Carl H. (Journal of Neurological Surgery Part B: Skull Base, 2018)
Objectives This study aimed to review endoscopic skull base surgeon experience with internal carotid artery (ICA) injuries during endoscopic endonasal surgery (EES) to provide an estimate of the incidence of ICA injury, the associated factors and identify the best training modalities for the management of this complication.Design Anonymous electronic survey of past participants at a well-established endoscopic skull base surgery course and a global online community of skull base surgeons.Main Outcome Measures Relative incidence of ICA injuries during EES, associated anatomic and intraoperative factors, and surgeon experience.Results At least 20% of surgeons in each surveyed population experienced a carotid artery injury. Reported carotid artery injuries were most common during tumor exposure and removal (48%). The parasellar carotid artery was the most commonly injured segment (39%). Carotid artery injuries were more common in high-volume surgeons, but only statistically significant in one of the two populations. Attendance at a skull base course or courses did not change the incidence of carotid artery injury in either surveyed population. In both surveys, respondents preferred live surgeries or active (not computer simulated) training models.Conclusions ICA injury is underreported and most common when manipulating the parasellar carotid artery for exposure and tumor dissection. Given the high morbidity and mortality associated with these injuries, vascular injury management should be prioritized and taught in a graduated approach by modern endoscopic skull base courses.
Keywords: skull base surgery; carotid artery; internal; carotid artery injuries; vascular system injuries